Jaccoud’s arthropathy in osteogenesis imperfecta - Martins, Frederico Rajão (2024)
Type I osteogenesis imperfecta is a genetic disease associated with mutations in the pro-alpha1 chains of type 1 collagen encoder gene COL1A1. It has an autosomal dominant pattern of inheritance, and leads to reduction in the amount of structurally normal collagen and subsequently, disorders of the extracellular membrane of skin, tendons and bone.